Development of optimal feeding management of early nursery culture of jade perch (Scortum barcoo McCulloch & Waite, 1917) in a recirculating system - Abdalroda, Firas Mahdi (2017)
Over and underfeeding have negative effects on growth and survival rates. So, optimum feeding management strategy is critical to achieving optimal fish growth, with reducing wastage. Two experiments were carried out in this study to investigate the optimal feeding frequency and rates of juvenile Jade Perch Scortum barcoo reared in a recirculating system (RAS). Each experiment was designed in a completely randomized design in triplicate and a fish were fed the same floating diets (contained 43% crude protein and 6% crude fat). For the first experiment, Jade Perch mean weight ± SE of 7.28 ± 0.13 g were fed different frequencies that included once, twice, three, or four meals a day at 5% body weight per day for 72 days. Each replicate contained 65 fish. After 72 d, the survival, growth, feeding efficiencies, body indices, plasma biochemistry, whole-body proximate composition, and muscle cholesterol were measured while histological sections of the liver were stained for glycogen with Periodic-acid Schiff (PAS). Results showed that growth was best when fish were fed three times a day, which was significantly higher than those fed one, two or four times a day. Feeding efficiencies were significantly better for fish fed two or three times a day. Plasma glucose, plasma cholesterol, PAS staining intensity of the liver, and hepatosomatic index were significantly higher for fish fed three times a day compared with once a day. Whole-body crude protein was significantly lower for fish fed once a day compared with treatments of two or four times a day. Muscle cholesterol tended to increase with increasing feeding frequencies, but the results were not significant. No significant treatment effect was detected on the plasma mineral content. Based on a feeding rate of 5% body weight/d, it is recommended that feedings are divided into three meals a day to increase available energy for optimal growth. The second experiment was conducted to investigate the optimal feeding rates of 2%, 4%, 6%, or 8% body weight per day for juvenile Jade Perch (average initial weight 7.45 ± 0.09 g). Each replicate contained 50 fish and the experimental duration was 100 days. The results indicated that weight gain and feed conversion ratio increased significantly (P< 0.05) as the rates of feeding were increased. Feeding rates had no effect on whole-body moisture, ash and protein, but crude lipid was significantly (P<0.05) higher in fish fed 8% per day. Although higher growth is achieved at 8% body weight per day, feeding efficiencies were reduced, which needs to be considered by the farmer depending on market demands and prices.